G6PD Variants and Haemolytic Sensitivity to Primaquine and Other Drugs - Bancone, Germana; Chu, Cindy S. (Frontiers in Pharmacology, 2021)
G6PD deficiency is the most common monogenic disorder in humans. This X-linked enzymatic defect was identified when similarities between the historic clinical syndromes of ‘favism’ and ‘primaquine sensitivity’ were recognized. G6PD deficiency is associated to acute haemolytic anaemia in the presence of oxidative stressors. The importance of haemolysis in G6PD deficient persons has increased as Plasmodium vivax endemic regions are moving towards elimination through use of 8-aminoquinolines, such as primaquine and tafenoquine. 8-aminoquinoline treatment regimens may be increasingly used among the vivax infected and healthy populations (if mass drug administration is deployed). Understanding the haemolytic mechanisms and risks associated to drug treatment will be crucial to provide treatment safely and widely. In this review we summarise the available data on drug-induced haemolysis accumulated in the last 70 years with a specific focus on the G6PD variants studied. Limitations of current laboratory and clinical characterisation as well as possible future research approaches are discussed.